Rebeldes con Pausa: Teresa de Jesús, Cervantes, Fray Luis, and the Curious Path to Holiness - Ana Laguna (Humanities, 2025)
Early modern theologians often cast female curiosity as both a moral flaw and an epistemic transgression. Aware of this suspicion, Teresa of Ávila professed to have renounced such dangerous impulses in her youth. Yet the persistent presence of curiosity in her writings suggests a strategic redeployment—one that fosters attentiveness and subtly renegotiates ecclesiastical authority as she actively advances reform within the Carmelite order. Through life-writing and scriptural exegesis, Teresa cultivates a disciplined appetite for knowledge: an appetite that outwardly conforms to, yet quietly subverts, doctrinal anxieties surrounding women’s intellectual desires. Her use of curiosidad moves fluidly between sacred and secular registers—sometimes connoting superficial fascination, at other times signaling a deeper, interior restlessness. Resisting reductive interpretation, Teresa reveals a sophisticated and self-aware engagement with a disposition both morally ambiguous and intellectually generative. The same culture that once feared her intellect would ultimately aestheticize it. After her death, Teresa’s relics were fragmented and displayed in Philip II’s Wunderkammer, transforming her once-condemned curiosidad into curiositas, an imperial collectible. Reading Teresa alongside her posthumous interpreters—Fray Luis de León and Miguel de Cervantes—this essay explores how her radical epistemological ambition reverberated through Spanish intellectual culture. Spanning this cultural arc—from sin to spectacle, from forbidden desire to sanctified display—Teresa emerges as a masterful theorist and activist reformer of spiritual authority. In these expansive roles, she reveals the immense and often contradictory power that curiosity wielded in the early modern world.